Congestive heart failure in children with pneumonia and respiratory failure. Issue 3 (6th November 2016) - Nimdet, Kachaporn; Techakehakij, Win
Abstract: Background: Congestive heart failure (CHF) is one of the most common cardiac complications of pneumonia in adulthood leading to increased risk of morbidity and mortality. Little is known, however, of CHF and pneumonia in children. The aim of this study was therefore to investigate the characteristics and factors associated with CHF in under‐5 children with pneumonia and respiratory failure. Methods: A retrospective cohort was conducted in hospitalized patients aged 2–59 months with community‐acquired pneumonia and respiratory failure from June 2011 to June 2014 at Suratthani Hospital, Thailand. The characteristics, therapeutic strategy, and clinical outcomes of CHF were reviewed. Baseline characteristics and basic laboratory investigations on admission were compared between the CHF and non‐CHF groups. Results: Of 135 patients, 14 (10%) had CHF. Compared with patients without CHF, the CHF group had prolonged intubation and hospital stay and high rates of associated complications such as ventilator‐associated pneumonia, sepsis, shock, and 30 day mortality. CHF was significantly associated with certain characteristics, including male sex and bacterial pneumonia. Conclusions: Pneumonia with respiratory failure is associated with CHF even in healthy children without cardiac risks. The awareness and early recognition of CHF, particularly in male, and bacterial pneumonia, is important in order to provide immediate treatment to reduce complications.